THE ANALYTICS OF CULTURE IN THE PHILOSOPHY OF “SILVER AGE” - Суходуб, Т. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the problem of social and culture ideas of representatives Russian “Silver age”. These ideas have actual meaning for contemporary epoch.